Women's experiences of economic coercion and depressive symptoms in Matlab, Bangladesh - Zara Khan; Yuk F. Cheong; Stephanie S. Miedema; Ruchira T. Naved; Kathryn M. Yount (Elsevier, 2020)
Prior studies of the association between intimate partner violence (IPV) and depressive symptoms have typically excluded economic coercion (EC), a prevalent form of IPV worldwide. Here, we used structural equation models (SEM) to estimate the association of EC with depressive symptoms, with and without adjustment for physical/psychological/sexual IPV, among women in rural Matlab, Bangladesh. Data were collected from cross-sectional surveys with married women 15-49 years, conducted between November 2018 and January 2019. Prior-week depressive symptoms were measured using the 10-item Centre for Epidemiologic Studies Depression short-form. Lifetime EC was assessed using a bi-dimensional, 36-item scale developed in Matlab. Lifetime physical/sexual/psychological IPV was assessed using the 20-item WHO Domestic Violence module. Covariates were age, age at marriage, and schooling; partner's schooling; and household wealth. Among 929 women, lifetime experience of EC ranged from 41.9% (control over access to work, schooling, and training) to 50.0% (control over use/maintenance of economic resources), while any lifetime physical/psychological/sexual IPV was 89.5%. Coercion involving the use and maintenance of economic resources had a significant, adjusted association with depressive symptoms (standardized coefficient = 0.491, p<0.001, R2=0.221). The standardized association of any physical/psychological/sexual IPV with depressive symptoms, adjusted for covariates and cluster sampling, was 0.346 (p <0.001, R2=0.143). When further adjusted for the two measures of EC, the association was attenuated and non-significant (0.049, p = 0.817). These findings suggest that EC is prevalent, significantly associated with depressive symptoms, and attenuates the association of other forms of IPV with depressive symptoms. Addressing EC with other forms of IPV may be necessary to reduce depressive symptoms in exposed women.